2020
DOI: 10.1128/msphere.00296-20
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Biofilm-Disrupting Nontypeable Haemophilus influenzae Vaccine Antigen Did Not Alter the Gut Microbiome in Chinchillas, Unlike Oral Delivery of a Broad-Spectrum Antibiotic Commonly Used for Otitis Media

Abstract: The use of broad-spectrum antibiotics to treat diseases, such as the highly prevalent pediatric disease otitis media (OM), contributes significantly to the worldwide emergence of multiple-antibiotic-resistant microbes, and gut dysbiosis with diarrhea is a common adverse sequela. Moreover, for many diseases, like OM, biofilms contribute significantly to chronicity and recurrence, yet biofilm-resident bacteria are characteristically highly resistant to antibiotics. The most cost-effective way to both prevent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…To address concerns about the potential to induce dysbiosis of the gut flora following active immunization with a vaccine antigen directed against a biofilm constituent (given that there are many 'good' biofilms on and in the human body as well), we immunized cohorts of chinchillas both via an subcutaneous and transcutaneous route with the same tip-chimer peptide to compare their gut microbiome to those that had been treated with the standard-of-care for OME (e.g., amoxicllin/clavulanic acid). We found that whereas orally administered amoxicllin/clavulanic did indeed rapidly induce dysbiosis of the gut flora, as expected, neither route of immunization with the DNABII-directed immunogen did so [56] which suggested that the induced antibodies did not likely transude onto the non-inflamed (non-diseased) mucosa that lined the GI tract with beneficial biofilms in these animals.…”
Section: Immunological Depletion Of Dnabii Disrupts Biofilms In Vivo:...supporting
confidence: 67%
“…To address concerns about the potential to induce dysbiosis of the gut flora following active immunization with a vaccine antigen directed against a biofilm constituent (given that there are many 'good' biofilms on and in the human body as well), we immunized cohorts of chinchillas both via an subcutaneous and transcutaneous route with the same tip-chimer peptide to compare their gut microbiome to those that had been treated with the standard-of-care for OME (e.g., amoxicllin/clavulanic acid). We found that whereas orally administered amoxicllin/clavulanic did indeed rapidly induce dysbiosis of the gut flora, as expected, neither route of immunization with the DNABII-directed immunogen did so [56] which suggested that the induced antibodies did not likely transude onto the non-inflamed (non-diseased) mucosa that lined the GI tract with beneficial biofilms in these animals.…”
Section: Immunological Depletion Of Dnabii Disrupts Biofilms In Vivo:...supporting
confidence: 67%
“…Whereas their focus was on antibodies that reduce carriage, and thus transmission of antibiotic-resistant bacteria [ 103 ], we envision use of specifically induced antibodies to release biofilm-resident NTHI from these highly resistant communities so they can be killed by host immune effectors and when necessary, traditional antibiotics, with the latter now used at a markedly reduced dose and for a shorter course due to the highly sensitive phenotype of NRel NTHI. An additional potential benefit of a less frequent antibiotic treatment regimen is reduction of off-target side effects and other undesirable sequelae of oral antibiotic use; which includes development of antibiotic resistance [ 84 , 104 ] and/or disruption of the gut microbiome [ 16 , [105] , [106] , [107] , [108] ].…”
Section: Discussionmentioning
confidence: 99%
“…Chinchillas were placed individually into clean cages, and fecal pellets were collected upon evacuation. Following collection, these samples were transferred immediately into sterile cryogenic vials by sterile forceps and stored at −80 °C until microbiota analysis [ 14 ].…”
Section: Methodsmentioning
confidence: 99%